ANALISIS MODEL PROMOSI BANK MUAMALAT INDONESIA TERHADAP MARKET SHARE KOTA BANDAR LAMPUNG - Rusliani, Rusliani (Jurnal Ekonomi Islam, 2017)
Shariah Bank have the potency to become the first option for customers to run their transactional banking option. It was showed by the acceleration development and growth of Shariah Banking in Indonesia. Along with the growth of Shariah Banking, a real competition among the Syariah Bank doers is unavoidable. Therefore a bank has to do efforts to be the main player on its segment, and able to provide major resources for its customers and eventually it binds satisfaction and loyalty. In such thigh competition, information plays an important role to attract customers or society to make use of the provided by the bank. The information of any form delivered by every stakeholder related to banking business. Therefore the market share can be gained by promoting Syariah Banks to those floating customer though an attractive and appropriate way. By doing such promotion with persistent and sustain, the possibility of the 5 % of market share which targeted by BI could be reached.